Immune Embedded Linux Core System with Multiple Sensors - Tao Gong (International Journal of Distributed Sensor Networks)
The security of the embedded Linux core system is more important than before because this system is becoming more useful to solve the security problem of the computer system than the Windows operating system. It is firstly necessary to identify the normal state of the embedded Linux core system with a model. In this paper, the normal model of this normal system is represented with the space-time property set of all the components in this system. For example, the space property of a file in this system is the absolute pathname of this file, and the time property of this file is its last revision time. This immune embedded Linux core system uses multiple sensors to detect some important information, such as the disaster features. This antidisaster system will be tested on the ARM11 chips.